LAW AS SIMULACRA: A POSTMODERNIST CRITIQUE OF THE DIGITALIZATION OF JUDICIAL PROCESSES - Setyawan, Vincent; Wisnubroto, Aloysius (FOCUS: Jurnal of Law, 2025)
The rapid digital transformation of judicial systems, especially through e-court, e-litigation, and AI, has improved efficiency but also raised philosophical concerns about law and justice. Drawing on Jean Baudrillard’s theory of simulacra and simulation, this study suggests that digitalized law risks creating a gap between procedural and substantive justice, as legal processes become technological representations detached from their humanistic and moral foundations. Using normative legal research and a postmodern philosophical approach, the study explores how digital judicial mechanisms manifest law as simulation. The findings indicate that digitalization prioritizes efficiency and procedural legitimacy but does not fully ensure substantive justice. The study calls for a philosophical critique to prevent the reduction of law to mere administrative technology. It emphasizes the need for ethical reinforcement, transparency, and public participation to preserve the true meaning of justice and safeguard its humanistic values.